2016
DOI: 10.3109/09638288.2015.1137978
|View full text |Cite
|
Sign up to set email alerts
|

A sense of increased living space after participating in multimodal rehabilitation

Abstract: According to these results, it is important to have various entrances to enhance change and to be aware of how these changes interact and can reinforce each other in order to facilitate the participants' empowerment processes toward a sense of increased living space. Implications for rehabilitation The efforts in MMR should be coordinated to be mutually reinforcing as changes in one area could facilitate in others and thus facilitate the participants' empowerment processes. Participants experience change after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
3
5
1
Order By: Relevance
“…In their own words, as they 'got their life back'. This is in agreement with another study where MMR led to feelings of empowerment and regained hope [31]. Other long-term effects on depression and several domains of life satisfaction are seen after MMR [32].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In their own words, as they 'got their life back'. This is in agreement with another study where MMR led to feelings of empowerment and regained hope [31]. Other long-term effects on depression and several domains of life satisfaction are seen after MMR [32].…”
Section: Discussionsupporting
confidence: 92%
“…The programme also led to improvement in their health. These results are supported by other studies of MMR, which show long-term positive effects on pain and disability [31,32].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In another primary care study, patients attributed the staff with having an important role in understanding individual needs and confidence-inspiring alliances (13). Ekhammar et al (14). studied experiences of change related to MMR and found that, after MMR, patients felt a sense of "increased living space".…”
mentioning
confidence: 99%